The second stain [anglicky] - Doyle, Arthur Conan Sir 1859-1930; Baudet, Stephanie, 1945- (The Sherlock Holmes children's collection, 2021)
Holmes shook his head sadly. You think that unless this document is found there will be war? Its very likely, said the prime minister. Then, sir, we must prepare for war. A secret government document has been stolen. Its up to Holmes and Watson to find it and save the country from war! But with sly secret agents, mysterious murders and the question of a curious bloodstain to contend with, will Holmes and Watson be able to piece the puzzle together in time?